Management Structure in the Film Industry - Mykhailiukova, Anastasiia; Antonivska, Maryna (Socio-Cultural Management Journal, 2024)
Introduction. The scientific and technological revolution and digitalisation introduced into various spheres of life also bring with them opportunities for creating completely new film content. The demand for cinema is constantly growing, as it is one of the most popular and profitable industries in the world. Purpose and methods. The purpose of the article is to identify the stages of contemporary film production organisation, determine the sequence of processes for creating a film product, analyse employees’ functions in the field of cinema, and substantiate a typical scheme of a film project organisational structure. The methodological basis of the study is the systemic and interdisciplinary approaches, as well as terminological, historical, calculation and constructive, structural and functional, and expert methods. Results. The stages of modern film production organisation are identified. The sequence of creating a film product processes on the way from creation to consumption is determined. The employees’ functions in the field of cinema are analysed. A typical scheme of a film project’s organisational structure for the perspective is substantiated. Conclusions. Summarising the scientific theoretical provisions on the organisation of management and a team of specialists in the field of cinematography, the article substantiates a flexible adaptive standard system for organising the filming process, which ensures effective interaction between various participants in the film making process, helps to avoid mistakes and delays in production, ensure compliance with the budget and deadlines, and deliver a high-quality film product that will be commercially viable for producers. In terms of scientific novelty, this study has significant potential for the development of management theory and practice, as well as for improving film production efficiency.